Authorities' Fiscal Forecasts in Latin America : Are They Optimistic? - Hadzi-Vaskov, Metodij; Ricci, Luca.; Werner, Alejandro; Zamarripa, Rene. (Washington, D.C. : International Monetary Fund, 2021)
Do governments in Latin America tend to be optimistic when preparing budgetary projections? We address this question by constructing a novel dataset of the authorities' fiscal forecasts in six Latin American economies using data from annual budget documents over the period 2000-2018. In turn, we compare such forecasts with the outturns reported in the corresponding budget documents of the following years to understand the evolution of fiscal forecast errors. Our findings suggest that: (i) for most countries, there is no general optimistic bias in the forecasts for the fiscal balance-to-GDP ratio (though there may be for the components); (ii) fiscal forecasts have improved for some countries over time, albeit they have worsened for others; (iii) in terms of drivers, we show that forecast errors for the fiscal balance-to-GDP ratio are positively correlated with GDP growth and terms of trade changes and negatively with GDP deflator surprises; (iv) forecast errors for public debt-to-GDP ratios are negatively associated with surprises to GDP growth; (v) lastly, budget balance rules seem to help contain the size of the fiscal forecast errors.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: Debt; Fiscal Policy; Foreign Exchange; Informal Economy; Underground Econom